2015
DOI: 10.1038/srep13827
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of miRNA-497 inhibits tumor angiogenesis by targeting VEGFR2

Abstract: Recent studies reported miR-497 exhibited inhibitory effects in various cancers. However, whether miR-497 is involved in inhibiting angiogenesis, which is critical for tumor growth and metastasis, is still unknown. The purpose of this study was to investigate the potential role of miR-497 in tumor angiogenesis. In this work, cell proliferation and apoptosis analyses were conducted to explore the potential function of miR-497 in HUVECs by using MTT and TUNEL assays. Western blotting (WB) was employed to validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…Several recently published studies have supported a role for microRNAs (miRNAs) in regulating fundamental normal and reactive cellular processes . Moreover, an increasing number of studies support a role for miRNA in the origination and progression of human cancers . Dysregulation of miRNA activity may result in progressive and uncontrolled tumour growth .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recently published studies have supported a role for microRNAs (miRNAs) in regulating fundamental normal and reactive cellular processes . Moreover, an increasing number of studies support a role for miRNA in the origination and progression of human cancers . Dysregulation of miRNA activity may result in progressive and uncontrolled tumour growth .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 98 miRNAs are located at different genomic regions involved in human tumorigenesis, suggesting that miRNAs are involved in the development and pathogenesis of malignancies, and could possibly serve as diagnostic or prognostic tumour biomarkers . Furthermore, miRNAs play critical roles in a variety of other cellular processes, including tumour growth, cell apoptosis and tumour cell metastasis, and can act as either oncogenes or anti‐oncogenes . Additionally, the expression profiles of different miRNAs in plasma, serum and tumour samples have been used to accurately classify human cancers, suggesting that miRNAs could possibly serve as biomarkers for diagnosing human cancers and developing a prognosis for cancer patients …”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are small (approximately 22 nucleotides in length), noncoding singlestranded RNA molecules that can regulate numerous biological processes, including cellular differentiation (Nolte-'t Hoen et al, 2015), proliferation (Zhao et al, 2012), apoptosis (Yeh et al, 2012), angiogenesis (Caporali and Emanueli, 2011), the development of cancer , and the inhibition of tumor angiogenesis and growth (Luo et al, 2013;Tu et al, 2015). Endometriosis is a common, although mysterious and fascinating, gynecological condition with diverse clinical manifestations and high variability.…”
Section: Discussionmentioning
confidence: 99%
“…However, detailed information concerning the role of miR-497 in the development of atherosclerosis is unknown. Recent study has shown that miR-497 in HUVECs induce apoptosis and inhibit the proliferation via targeting VEGFR2/Raf/MEK/ERK signal pathway[13]. But that doesn’t represent it is the only way to affect the functions of ECs.…”
Section: Introductionmentioning
confidence: 99%